Analytical study of stock price movement in the Iraq Stock Exchange (Study of a sample of banks) - Shaebith, Razzaq Dhiab; Taha, Hibayousif (International Journal of Psychosocial Rehabilitation, 2020)
The research discussed analysis of stock prices in the Iraq Stock Exchange, an applied sample of Iraqi banks listed on the Iraq Stock Exchange, by the commercial bank, from 2018 to 2019. Daily share prices were used, the main purpose was to analyze the sectors whose shares are listed in the financial market, use of Box-Jenkins, methodology to forecast stock prices on a daily basis,the study found that raising bank capital, according to the instructions of the Central Bank of Iraq, it provides greater protection for depositors, by the expense of the bank’s profitability,raising capital requires injecting new shares into the financial market, in the economic point, oversupply negatively affects stock prices, at the limited private banking activity, the increase in the number of companies listed on the market has nothing to do with the number of shares, and not even its value in terms of high and low, the increase in the number of companies whose shares are traded in 2019, however, the number and value of shares traded were low compared to the same year. The study also concluded that the Box- Jenkins methodology should be used, as the future prices forecasting of stock prices can be Forecasted objectively, approximating reality,the most appropriate model through which to make a forecastingwas 2,1,1 for the commercial bank.